Pengembangan Aplikasi Rekomendasi Kolam Renang menggunakan Metode Topsis Borda - Yehezkiel Windriono; Ratih Kartika Dewi; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Swimming is a sport which done in water, either in fresh water or sea water. There is somewhat problem in choosing a swimming pool based in people's interest due to many available swimming pools in Malang city. Each swimmer in a group who had different preference on swimming pool also complicates the process of choosing pool among groups.There are three factors which affects people's interest in choosing swimming pool such as distance, ticket price, and pool's rating. Therefore, the solution to choosing swimming pool is by developing an Android based group decision support system. The system generates swimming pool group recommendation using Topsis Borda method. The system also uses criterias such as distance, ticket price, and pool's rating as reference for Topsis method. Distance criteria provided by measuring distance between user's location and swimming pool's location using GPS, thus the developed application is a location based service. The generated recommendations displays informations such as pool's name, a photo, distance between user and pools, ticket price, and pool's rating. Blacbox testing on implemented system reached 100% of functional validity. Algorithm validation testing is considered to be valid because the manual count and implemented Topsis Borda method count in the system shows the same results. Lastly, the usability testing on the implemented system obtained 84.5 score from five respondents. That score shows that system is on B grade, with user acceptance category as acceptable, and adjective rating as excellent on SUS Score.